النموذج الياباني وأزمته الأقتصادية (المجلة العراقية للعلوم الاقتصادية, 2018)
The successful Economic Models of Japan and Germany are classified among the best ones from the point of view of Economists and politicians-Though the two countries differ from many aspects, they have some common features. In this study we try to explore the possibility of applying the positive aspects of Japanese Experiment on Iraqi Economy. The study falls into three sections. The first one deals with the factors of success in Japan. While the second devoted to study the structure of Japanese Economy and third section displays the crisis of Japanese Economy.